Luteolin, a flavonoid from Syzygium myrtifolium Walp. - Raden Herni Kusriani; Shinta Maulida Rosandhy; Elfahmi (Current Research on Bioscences and Biotechnology, 2019)
A flavonoid, luteolin, was isolated from the leaves of Syzygium myrtifolium . The compound was purified using vacuum liquid chromatography with the help of a specific guidance for the flavonoid isolation. The chemical structure of this compound was determined based on measurements of UV, IR and NMR spectroscopic data. The occurrence of luteolin in S. myrtifolium is firstly reported from this study.